Fair, square & legal : safe hiring, managing & firing practices to keep you & your company out of court - Weiss, Donald H., 1936- (New York : American Management Association, 1995)
Fair, Square & Legal is a concise, one-stop guide to what you as a manager should and shouldn't do if you want to stay clear of trouble. This revised edition has been thoroughly updated throughout, and provides new coverage of the Family and Medical Leave Act, the Civil Rights Act of 1991, and the Americans with Disabilities Act. Written by an experienced manager, the book translates complex legal issues and precedents into a set of easy-to-follow guidelines for managing people. It provides both an overview of safe managerial procedures and a quick look-up source for specific situations you may encounter. The book encompasses a broad range of potential problem areas. For each, author Donald H. Weiss supplies non-legalese definitions of key terms, practical guidelines for what to say and do, fictionalized stories that illustrate both problems and solutions, and actual case studies of precedent-setting court decisions.
Safe Hiring Practices -- Safe Recruiting Practices -- Safe Interviewing Practices -- Safe Employment Decisions -- Preventing Sex Discrimination in Hiring -- Preventing Negligent Hiring -- Safe Management Practices -- Safe Evaluations and Promotions -- Safe Management, the Right to Privacy, and Defamation -- Safe Management of Family and Medical Leave -- Preventing Sex Discrimination and Sexual Harassment on the Job -- Mismanaging People with Disabilities -- Employee Action Rights and Labor Laws -- The Uniformed Services Employment and Reemployment Rights Act of 1994 (USERRA, 38 U.S.C. [sections] 4301-4333) -- Safe Firing Practices -- Safe Discipline and Firing Practices -- Public Policy -- Managing a Reduction in Force -- Safe Management of Older Employees -- What Civil Rights and Other Personal Protection Laws Say.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Labor laws and legislation -- United States; Personnel management -- United States; Personnel -- Direction -- États-Unis.; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal Services; LAW -- Civil Procedure; LAW -- Administrative Law & Regulatory Practice; Labor laws and legislation; Personnel management; United States